2015
DOI: 10.1353/lan.2015.0007
|View full text |Cite
|
Sign up to set email alerts
|

Ancestry-constrained phylogenetic analysis supports the Indo-European steppe hypothesis: Supplementary materials

Abstract: The supplementary materials contain details of our BEAST analyses. Note that in addition to the four blocks of analyses (A-D) mentioned in Experiments ( §6), there is a fifth block of eight analyses (E1-8) in which each ancestral language in A1, in turn, has its ancestry constraint removed. This document contains the following: S.1 A synopsis of elements that vary between analyses. S.2 A description of accompanying electronic files. S.3 Summary trees and summary statistics for each phylogenetic analysis. S.1 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Manually produced cognate sets have nearly always constituted the input data to the Bayesian approaches, but judgments about cognacy may vary among scholars and these judgments directly influence the structure and quality of the phylogeny inferred. For instance, correction of the lexical data [12] for both lexical errors and cognate judgments showed that the corrected datasets can lead to ages that are different-both younger and significantly different in terms of the Bayes Factor criterion [22]-from the original ages inferred based on the original dataset [14]. This result has been confirmed in [13], a paper that used a different set of tree priors but nevertheless reached similar conclusions as [12].…”
Section: Plos Onementioning
confidence: 79%
See 4 more Smart Citations
“…Manually produced cognate sets have nearly always constituted the input data to the Bayesian approaches, but judgments about cognacy may vary among scholars and these judgments directly influence the structure and quality of the phylogeny inferred. For instance, correction of the lexical data [12] for both lexical errors and cognate judgments showed that the corrected datasets can lead to ages that are different-both younger and significantly different in terms of the Bayes Factor criterion [22]-from the original ages inferred based on the original dataset [14]. This result has been confirmed in [13], a paper that used a different set of tree priors but nevertheless reached similar conclusions as [12].…”
Section: Plos Onementioning
confidence: 79%
“…The choice of working with the short, 40-item word lists of the ASJP database [25] rather than longer word lists is a motivated one. We considered using publicly available datasets that have cognate sets for longer lists of meanings, including databases of Indo-European [12] (210 items), Bantu [26] (100 items), Austronesian [10] (210 items), and Pama-Nyungan languages [27] (200 items). However, these datasets are limited to a few language families, do not cover all calibration points listed in Table 1, and do not share the same set of meanings.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations